2011
DOI: 10.1901/jaba.2011.44-69
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fixed Momentary Dro Schedules Under Signaled and Unsignaled Arrangements

Abstract: Fixed momentary schedules of differential reinforcement of other behavior (FM DRO) generally have been ineffective as treatment for problem behavior. Because most early research on FM DRO included presentation of a signal at the end of the DRO interval, it is unclear whether the limited effects of FM DRO were due to (a) the momentary response requirement of the schedule per se or (b) discrimination of the contingency made more salient by the signal. To separate these two potential influences, we compared the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Future research should also examine the use of signals during resetting and non‐resetting DRO intervals. Previous research (Hammond et al, ) has shown that signals can influence the effects of other DRO schedules (i.e., fixed momentary DRO). In the current study, a timer was visible to the participant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research should also examine the use of signals during resetting and non‐resetting DRO intervals. Previous research (Hammond et al, ) has shown that signals can influence the effects of other DRO schedules (i.e., fixed momentary DRO). In the current study, a timer was visible to the participant.…”
Section: Resultsmentioning
confidence: 99%
“…Differential reinforcement of other behavior (DRO) is a decelerative behavioral intervention that involves delivery of a reinforcer contingent upon the absence of the target behavior during a given interval (Repp & Deitz, ). DRO is among the most‐commonly used decelerative behavioral interventions (Matson et al, ) and has been shown to effectively decrease a wide variety of behavioral excesses, including self‐injury (Cowdery, Iwata, & Pace, ), stereotypy (Repp, Deitz, & Deitz, ), aggression (Hammond, Iwata, Fritz, & Dempsey, ), motor tics (Capriotti, Brandt, Ricketts, Espil, & Woods, ), disruptive classroom behavior (Austin, Groves, Reynish, & Francis, ), and sibling conflict (Leitenberg, Burchard, Burchard, Fuller, & Lysaght, ). Several factors can influence the efficacy of a DRO procedure, including the duration of the DRO interval, the inclusion of an extinction component, reinforcer selection (function‐based versus arbitrary), and delivery of pre‐session rules (Watts, Wilder, Gregory, Leon, & Ditzian, ).…”
Section: Introductionmentioning
confidence: 99%
“…Much research on momentary‐based schedules of reinforcement has focused on the reduction of problem behavior (e.g., momentary differential reinforcement of other behavior; Conyers, Miltenberger, Romaniuk, Kopp, & Himle, ; Hammond, Iwata, Fritz, & Dempsey, ; Lindberg, Iwata, Kahng, & DeLeon, ; Toussaint & Tiger, ). In this study, we increased compliance with a cluster instruction by momentarily supervising the participant and providing tokens for completed math problems and on‐task behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have recently evaluated the effects of adding discriminative stimuli to signal either when the DRO is in place (Della Rosa, Fellman, DeBiase, DeQuinzio, & Taylor, ) or the onset of a specific procedural component within the DRO arrangement (Hammond, Iwata, Fritz, & Dempsey, ). Hammond et al () compared momentary DRO (mDRO) with and without a signal that preceded reinforcer delivery. The signal consisted of the experimenter holding the reinforcer above her head.…”
Section: Original Conceptsmentioning
confidence: 99%
“…In the mDRO evaluated by Hammond et al (), the signal specified brief periods in which problem behavior reset the interval, possibly resulting in discriminated responding rather than general suppression of target behavior. An alternative is to arrange the DRO so that any target responses (both before and after the signal onset) reset the programmed interval.…”
Section: Original Conceptsmentioning
confidence: 99%